Close the Gap, 2002 (2002)
2002 1960-2000 "Close the Gap, 2002" [EP0201a], 2002 The Close the Gap campaign in Scotland started in 2001. The project partners included the Scottish Executive, Scottish Enterprise, Scottish Trades Union Congress, Highlands and Islands Enterprise and the Equal Opportunities Commission.